Mechanism of neuronal remodeling in Drosophila dendrite arborization neurons. - Li, Ming Hao. (2010)
Developmental neuronal remodeling has gained increasing research interest in recent years. In-depth understanding into its mechanisms may offer potentials for an ultimate cure for neurodegenerative diseases. Some neurons can regrow their axons or dendrites after pruning to rewire the neuronal circuit. The molecular mechanisms underlying this process remain poorly understood. In a large-scale RNAi screening in Drosophila melanogaster, peripheral sensory neurons was examined during metamorphic dendrite pruning to explore novel pathways that may be involved in dendritic pruning. Epifluorescence and confocal microscopy was employed to image the pupal neurons. A number of new genes were identified to be capable of affecting the dendritic pruning, and investigations into these genes may provide some insights for future research.